Pravastatin Prevents Increases in Activity of Metalloproteinase-2 and Oxidative Stress, and Enhances Endothelium-Derived Nitric Oxide-Dependent Vasodilation in Gestational Hypertension - Toghi, Cristal Jesus [UNESP]; Martins, Laisla Zanetoni [UNESP]; Pacheco, Leonardo Lopes [UNESP]; Caetano, Edileia Souza Paula [UNESP]; Mattos, Bruna Rahal; Rizzi, Elen; Dias-Junior, Carlos Alan [UNESP] (MDPI, 2023)
Pre-eclampsia (PE) is a hypertensive disorder of pregnancy and has been associated with placental growth restriction. The pre-eclamptic placenta releases free radicals to maternal circulation, thus increasing oxidative stress. An impaired redox state leads to reduction in circulating nitric oxide (NO) levels and activation of extracellular matrix metalloproteinases (MMPs). However, activation of MMPs induced by oxidative stress is still unclear in PE. Antioxidant effects have been demonstrated with the use of pravastatin. Therefore, we hypothesized that pravastatin protects against oxidative stress-induced activation of MMPs in a rat model of PE. The animals were divided into four groups: normotensive pregnant rats (Norm-Preg); pregnant rats treated with pravastatin (Norm-Preg + Prava); hypertensive pregnant rats (HTN-Preg); and hypertensive pregnant rats treated with pravastatin (HTN-Preg + Prava). The deoxycorticosterone acetate (DOCA) and sodium chloride (DOCA-salt) model was used to induce hypertension in pregnancy. Blood pressure, and fetal and placental parameters were recorded. The gelatinolytic activity of MMPs, NO metabolites and lipid peroxide levels were also determined. Endothelium function was also examined. Pravastatin attenuated maternal hypertension, prevented placental weight loss, increased NO metabolites, inhibited increases in lipid peroxide levels, and reduced the activity of MMP-2, and these effects were observed along with enhanced endothelium-derived NO-dependent vasodilation. The present results provide evidence that pravastatin protects against activation of MMP-2 induced by oxidative stress in pre-eclamptic rats. These findings may also involve improvement in endothelial function related to NO and antihypertensive effects of pravastatin, thus suggesting pravastatin as a therapeutic intervention for PE.
Keywords: antioxidant; gestational hypertension; metalloproteinases; pravastatin